Pengaruh Sikap, Persepsi Keamanan, Dan Kepercayaan Terhadap Minat Penggunaan Pinjaman Online Pada Anggota Kelompok Tani - Warsono, Khodijah; Adi Wibowo, Purwo (Universitas PGRI Yogyakarta, 2025)
This study aims to analyze the effect of attitudes, perceived security, and trust on interest in using online loans for farmer group members. The object of research is members of farmer groups in the Pakis Aji sub-district area who have and have not taken online loan credit. Data was obtained through a survey method and using cluster sampling technique so that a sample of 100 respondents was obtained. The results of this study indicate that attitude has no effect on interest in using online loans, while perceived security and trust have a significant positive effect on interest in using online loans.